Cellular Microbiology: The metabolic interface between host cell and pathogen. (7th July 2019) - Russell, David G.
Abstract: Cellular Microbiology has benefited greatly from the use of immortalized cell lines as host cells for tissue culture models of infection. However, these cells lack many important characteristics of the different cell lineages that are found in vivo. This deficiency is particularly true of macrophages that we now know derive from several distinct ontogenic lineages. This perspective discusses these challenges and possible approaches to overcome them.